Manajemen Berbasis Sekolah Melalui Pemberdayaan Masyarakat dan Peran Komite Serta Tantangan Pelaksanaannya - Lestariningtyas, Lestariningtyas (PGRI Kota Semarang, 2024)
The aim of this research is to explore the implementation of School Based Quality Management through community empowerment and the role of committees. research methods in descriptive analysis. School Based Management (SBM) is a management model that provides greater autonomy to schools, provides flexibility/flexibility to schools, and encourages direct participation of all school members (teachers, students, principals, employees) and the community (parents of students , entrepreneurs, and so on) to improve the quality of schools. The principles in school-based management are autonomy, flexibility, participation and initiative. School Based Management (SBM) cannot be separated from the characteristics of effective schools. Therefore, the characteristics of SBM include inclusively the elements of an effective school which are categorized into input, process and output